PENYUSUNAN BALANCED SCORECARD SEBAGAI PENGUKURAN KINERJA PADA PMI TULUNGAGUNG - Hariwibowo, Ignatius Novianto; Kurniahardi, Katharina Nindita (Universitas katolik Musi Charitas, 2024)
The purpose of this service is to help formulate performance measurement tools using the Balanced Scorecard (BSC) at the Indonesian Red Cross (PMI) Tulungagung. Creating quality public services is a challenge for nonprofit organizations today. PMI is one of the non-profit organizations formed by the Government of Indonesia to receive demands to improve public services amid existing limitations. Therefore, the formulation of the direction of the strategic work plan is needed to achieve the objectives of PMI Tulungagung. The formulation of the strategic performance plan is prepared with the BSC approach at PMI Tulungagung. The results of this service are key performance indicators that can be applied by PMI. Then, in this PMI, the financial perspective is a basic perspective that supports internal learning and processes to achieve service satisfaction.